How e-WOM Shapes Travel Intentions: A Cross-Sectional Study of Cultural Heritage Sites on Social Media - Yubo, Shao; Jamal Rizal, Razali; Hasmadi, Hassan; Bo, Pan (People & Global Business Association, 2025)
Purpose: Cultural heritage sites face declining public engagement in the digital era, threatening their preservation and transmission. While social media offers new avenues to revitalize interest, existing studies rarely explore how information characteristics—such as source credibility, information source, and argument quality—interact with gender to shape the effectiveness of electronic word-of-mouth (e-WOM) in heritage tourism. This study addresses this gap by examining how these factors influence tourists' intentions to visit cultural heritage destinations in China. Design/methodology/approach: A cross-sectional survey was conducted with 242 tourists in Hebei Province. Structural equation modeling (SEM) using Smart-PLS 4.0 was employed to assess the direct and mediated effects of information characteristics on travel intention through positive e-WOM, along with gender moderation. Findings: Results reveal that information source (β = 0.227), source credibility (β = 0.301), and argument quality (β = 0.229) significantly enhance positive e-WOM, which in turn increases travel intention (β = 0.251). Gender moderates this relationship (β = 0.500), with females showing greater responsiveness to positive e-WOM. Research limitations/implications: Limitations include the geographic scope and self-reported data. Future research should expand to cross-cultural contexts and adopt longitudinal designs. These findings offer actionable strategies to enhance digital engagement in heritage preservation while extending the theoretical understanding of e-WOM in tourism. Originality/value: This study contributes a triadic model linking message credibility, source authority, and content persuasiveness to e-WOM-driven travel behavior. Gender differences further highlight the need for audience-tailored communication strategies. Practically, heritage tourism marketers should prioritize credible expert-generated content and gender-sensitive campaigns, particularly on platforms like Douyin